Detection of Hepatitis C Virus RNA in Blood Donors with Nested PCR Technique - Supiana Dian Nurtjahyani; Mochammad Amin Amin; Retno Handajani Handajani (Biomedical Engineering, 2016)
Objective: This study was conducted to detect hepatitis C virus (HCV) RNA among blood donors in Tuban, East Java, Indonesia,  using nested Polymerase Chain Reaction (PCR) technique.Material and methods: Seven blood donors  with positives anti-HCV were obtained from 500 blood donors from Red Cross Blood Donor Center (Palang Merah Indonesia = PMI) Tuban, East Java, Indonesia, consisting of 375 men (75%) and 125 women (25%). Detection of anti-HCV antibody prevalence in the blood donors was done by using Enzyme-Linked Immunosorbent Assay (ELISA).  The detection of HCV RNA in blood donors  sera  with positives  anti-HCV were performed using nested-PCR technique with three set of primer pairs targeting the NS5B and 5’UTR regions of HCV.  Further amplification products were visualized on a 2% agarose gel containing ethidium bromide under  UV illumination.Result: Seven positives anti-HCV blood donors sera (1.4%) were obtained from 500 blood donors sera, in PMI Tuban, East Java, Indonesia. Out of seven blood donors sera with positives anti-HCV, 6 sera (85,7%)  were positives HCV RNA by using nested PCR technique. Five HCV RNAs were detected with two set of primers based on NS5B HCV region and 1 positive HCV RNA was detected with another set of primer based on 5’UTR HCV region.Conclusion: HCV RNAs were detected in 85,7% positives anti-HCV blood donors using nested PCR technique, in PMI Tuban, East Java. Further research is needed to determine the  genotype  and  subtype  of  HCV.